2021
DOI: 10.3389/fphar.2020.609825
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics of Platycodon grandiflorum and its Mechanism in Lung Cancer Treatment

Abstract: Objective: The technology, network pharmacology and molecular docking technology of the ultra performance liquid chromatography-quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF-MS/MS) were used to explore the potential molecular mechanism of Platycodon grandiflorum (PG) in the treatment of lung cancer (LC).Methods: UPLC-Q-TOF-MS/MS technology was used to analyze the ingredients of PG and the potential LC targets were obtained from the Traditional Chinese Medicine Systems Pharmacology database, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Twenty-one genes associated with flavonoids biosynthesis were up-regulated, and 44 phenylpropanoid biosynthesis-related genes were up-regulated. The active ingredients of PG were mainly concentrated in terpenoids, flavonoids, and phenolic acids, 18,52 and saponins were mainly pentacyclic triterpenoids, such as platycodon D and polygalacinn D. Flavonoids were mainly apigenin and lutein, and phenolic acids were ferulic acid, isoferulic acid, chlorogenic acid, and caffeic acid. 12 The up-regulated expression of terpenoids, flavonoids, and phenolic acid-related genes in PGn could promote the production of more saponins, flavonoids, and phenolic acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one genes associated with flavonoids biosynthesis were up-regulated, and 44 phenylpropanoid biosynthesis-related genes were up-regulated. The active ingredients of PG were mainly concentrated in terpenoids, flavonoids, and phenolic acids, 18,52 and saponins were mainly pentacyclic triterpenoids, such as platycodon D and polygalacinn D. Flavonoids were mainly apigenin and lutein, and phenolic acids were ferulic acid, isoferulic acid, chlorogenic acid, and caffeic acid. 12 The up-regulated expression of terpenoids, flavonoids, and phenolic acid-related genes in PGn could promote the production of more saponins, flavonoids, and phenolic acids.…”
Section: Discussionmentioning
confidence: 99%
“…3,11 Triterpenoid saponins have been discovered in PG with multiple pharmacological activities and clinical therapeutic effects. 12,13 Modern pharmacological research has shown that PG has anti-inflammatory, 14 antioxidant, 15 liver protection, 16,17 anti-tumour, 18 and anti-obesity effects. 19 Annual PG is mainly used as a food; PG is used as a medicine when the roots reach 2 or 3 years in age or more.…”
mentioning
confidence: 99%
“…erefore, this experiment used FA as raw material, and the chemical composition was determined by UPLC-QTOF-MS/MS. In addition, the active ingredient, disease target, and the action pathway were investigated to obtain the underlined mechanism used by FA on MDD, which was further verified by molecular docking [15][16][17].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, network pharmacology has been widely used in the study of Chinese medicine anti-SARS-CoV-2 [ 8 ]. The emerging network pharmacology technology can be widely used to explore the possible mechanism of Chinese medicine to treat diseases through multicomponent, multitarget, and multichannel levels and to explore potential therapeutic drugs [ 9 ]. The Chinese medicine injections in the New Coronary Virus Pneumonia Treatment Programme (Trial 7) [ 10 ] are included in the recommended SARS-CoV-2 treatment options, such as Xiyanping injection, Xuebijing injection, Reduning, Tanreqing injection, Xingnaoling injection, Shenfu injection, Shenmai injection, and Shengmai injection.…”
Section: Introductionmentioning
confidence: 99%